Remarks by World Bank Group President David Malpass at the 2nd Global COVID-19 Summit - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass at the 2nd global Coronavirus disease 2019 (COVID-19) summit. He discusses: the World Bank Group is working hard to support developing countries with their health programs. Looking ahead, the new financial intermediary fund (FIF) - for pandemic prevention, preparedness, and response at the World Bank will complement the financing and technical advice - core instruments that strengthen health systems and preparedness. With support from the G20, the Bank is proceeding quickly to develop the FIF, working with interested governments, the World Health Organization (WHO), and other partners. To achieve better health outcomes, developing countries need strong political leadership, commitment, and consistent domestic investments. They also need more financial support from the international community to build capacity.